War and sacrifice
1 online resource (xiv, 224 pages)
Keywords: This volume covers conflicts from sub-Neolithic Finland to early Modern Ireland, looking at the archaeological evidence for conflict. This evidence ranges from excavation, to osteology, to artefacts, to linguistics, bringing together varying approaches to the study of conflict in the past. Most of the papers relate to prehistory, starting with the sub-Neolithic, running through the Bronze Age and into the Iron Age. There are also papers on Irish conflict archaeology, running from the sixteenth century AD to the 1916 Easter Rising. The prehistoric papers are significant in examining the evidence forensically and trying to establish whether conflict is the best explanation for particular phenomena, while the Irish papers open the rich landscape of conflict in Ireland, with all of the possibilities for investigating conflict that can be found.